Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1088/1361-6528/aa800f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an ideal nanoring from a black phosphorus nanoribbon upon movable bundling carbon nanotubes

Abstract: As a low dimensional material, black phosphorus (BP) continues to attract much attention from researchers due to its excellent electric properties. In particular, the one-dimensional material, in the form of a ring or tube formed from BP, has been extensively studied and found to be a perfect semiconductor. But the BP ring has never been reported in laboratories. To form an ideal ring from a rectangular BP ribbon, we choose a carbon nanotube (CNT) bundle to attract the ribbon and move one or more CNTs in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…When chemical synthesis approaches are difficult to obtain a BP nanotube, physical fabrication methods are worth trying. Cai et al [25][26][27] proposed an approach to obtain a BP nanotube from a rectangular BP ribbon. In their work, a rectangular BP ribbon putting nearby a CNT moves toward and curves upon the CNT under their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…When chemical synthesis approaches are difficult to obtain a BP nanotube, physical fabrication methods are worth trying. Cai et al [25][26][27] proposed an approach to obtain a BP nanotube from a rectangular BP ribbon. In their work, a rectangular BP ribbon putting nearby a CNT moves toward and curves upon the CNT under their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to carbon nanotubes (CNTs) being formed from curved graphene ribbon, a BP nanotube [13,14,15,16,17,18,19,20,21,22,23,24,25,26] may also be obtained by curling a single-layer black phosphorus ribbon and bonding the closing neighbour edges. One of the merits of the new phosphorus allotrope is that the tube has fewer unsaturated atoms, which are essential to the thermal and chemical stabilities of the material [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the physical assembly approach could be worth trying. To obtain a BP nanotube, Cai et al [23,24,25] tested several approaches to produce a nanotube from a rectangular BP ribbon. They [23] found that to form a perfect BP nanotube on a specified CNT, a rectangular BP ribbon with a perfect length is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Unfortunately, a BP nanotube (BPNT) has never been discovered to date. Recently, people suggested a potential way to obtain BPNTs in using numerical simulation approaches, [20][21][22][23][24][25] and it is similar to the synthesis of CNTs via tailoring graphene experimentally. 26 For example, an armchair BPNT can be obtained by winding a BP ribbon along the armchair direction on a CNT.…”
Section: Introductionmentioning
confidence: 99%